Correlation between full-thickness degenerative supraspinatus tear and radiographic parameters including the acromiohumeral centre edge angle and the greater tuberosity angle - Chaiyanun Vijittrakarnrung (2022)
Background: Many radiographic parameters associated with the extrinsic cause of supraspinatus tears have been proposed. The aim of this study was to assess the relationship between a full-thickness degenerative supraspinatus tear (FTDST) and the patient’s radiographic parameters, including the acromiohumeral centre edge angle (ACEA) and the greater tuberosity angle (GTA). Methods: A retrospective study was conducted. We included 116 patients who underwent shoulder arthroscopic surgery at our institute. The case group included FTDST patients, whereas the control group also included patients without evidence of supraspinatus tears. In each patient, the ACEA and GTA values were measured and analyzed by two independent observers. Intra- and interobserver reliabilities were assessed. Multivariate regression analysis was performed. Results: The ACEA values were significantly increased in the FTDST group with a mean of 26.44° ± 9.83° compared with 16.81° ± 7.72° in the control group (P < 0.001). Multivariate regression analysis also showed that higher ACEA values were associated with an FTDST (odds ratio 1.16 per degree, P = 0.01). For GTA values, a statistically significant difference was found with a mean of 70.92° ± 6.64 compared with 67.84° ± 5.56 in the control group (P = 0.02). However, stepwise regression analysis did not indicate that GTA was a predictor of FTDST. Conclusions: Our study demonstrated that the presence of increased ACEA values is an independent significant risk factor for the presence of FTDSTs. Consequently, GTA values may be less helpful in assessing the risk of FTDST, especially in this specific population.